EVALUASI KECERNAAN IN-VITRO DAN KANDUNGAN NUTRIEN PADA LAMTORO MINERAL BLOK (LMB) SEBAGAI PAKAN SUPLEMEN UNTUK TERNAK RUMINANSIA - Joseph G. (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2020)
The purpose of this study was to evaluate digestibility in vitro and to analyze the nutrient content of lamtoro mineral block (LMB) as a feed supplement in ruminants. The research was carried out at the Laboratory Department of Animal Husbandry, Faculty of Agriculture, Pattimura University. To determine the nutrient content of LMB, a proximate analysis was carried out at the Center for Biological Resources and Biotechnology Research, and to determine the digestibility of LMB, an in-vitro test was carried out at the Dairy Animal Nutrition Laboratory, IPB, University. The observation variables in this study, namely the nutrient content, were crude protein, crude fiber, crude fat, water content and ash from the LMB. Meanwhile, the digestibility was dry matter digestibility, organic matter digestibility, VFA and N-NH3 production. The experimental design used was a descriptive design. The results showed that LMB had good nutrient content, namely high protein (> 20%), low crude fiber (Â± 5%), high dry matter digestibility (> 75%) and VFA production was still in the normal range. . Based on the results of this study, it can be concluded that the LMB can be used as a supplement feed for ruminants as a source of protein.